An evaluation of a community-based forest restoration programme in Gunung Gede Pangrango National Park, West Java, Indonesia - Tintin Retno Pramesti; Rita Retnowati; Dolly Priatna (Universitas Pakuan, 2020)
Forest restoration is needed to improve the condition of degraded ecosystems and boost up the ecological services. The existence of forest areas, especially in Indonesia, cannot be separated from the livelihoods of the people living around them. The purpose of this study was to evaluate whether the feasabiluty of the community-based forest restoration programme, implemented by the Gunung Gede Pangrango National Park Agency (BBGGPNP) and its partners, is feasible and can support efforts to restore forest ecosystem functioning and build community independence in managing the forest ecosystem. This study used the Context, Input, Process and Product (CIPP) method. This is an evaluation model which provides an analytical and rational basis for programme decision-making, based on a cycle of planning, structuring, implementing and reviewing and revising decisions, examined through a different aspect of evaluation –context, input, process and product evaluation. Data were obtained from field observations, interviews and document analysis. Aspects of the programme ‘Context’ were found to be categorized as good and can become the basis for programme implementation, Programme ‘Inputs’ were also determined to be good, and fulfilled the criteria required to support the achievement of programme objectives. The ‘Process’ aspects were found to be sufficient, with key areas for improvement included the need for better coordination with partners and the need to respond to technical restoration requirements by adjusting the area of land to be restored, the number of trees to be planted, and by considering the technical rule of restoration. The ‘Product’ aspect of the programme were shown to be good, is shown by the achievement of the target amount and growth of trees and the increased capacity of human resources as well as the development of independent businesses in the ex-encroachers who were the programme participants. Based on these results, it can be concluded that the community-based forest restoration programme such as conducted by the GGPNP Agency is feasible and can be implemented in similar sites.Restorasi hutan diperlukan untuk memperbaiki fungsi ekosistem hutan yang terdegradasi. Keberadaan kawasan hutan, khususnya di Indonesia, tidak dapat dipisahkan dengan penghidupan masyarakat yang tinggal di sekitarnya. Tujuan dari penelitian ini adalah untuk mengevaluasi apakah program restorasi hutan berbasis pemberdayaan masyarakat yang dilaksanakan oleh Balai Besar Taman Nasional Gunung Gede Pangrango (BBTNGGP) bersama mitranya, layak serta dapat mendukung upaya pemulihan ekosistem dan membangun kemandirian masyarakat. Penelitian ini menggunakan metode CIPP, yaitu model evaluasi pada aspek Context, Input, Process dan Product. Data diperoleh dari hasil observasi lapangan, wawancara dan analisa dokumen. Berdasarkan analisis data, dapat disimpulkan bahwa program restorasi hutan berbasis pemberdayaan masyarakat layak untuk diterapkan sebagai upaya memulihkan ekosistem dan membangun kemandirian masyarakat di sekitar hutan. Aspek Konteks program berkategori baik dan dapat menjadi dasar utama pelaksanaan program, Aspek Input program baik, telah memenuhi kriteria yang mendukung tercapainya tujuan program, Aspek Proses berkategori cukup, perlu melakukan koordinasi yang lebih baik dengan pihak mitra untuk lebih berkomitmen dan perlu untuk melakukan penyesuaian antara target luasan lahan yang direstorasi dengan jumlah pohon yang ditanam dengan mempertimbangkan aturan teknis restorasi. Aspek Produk berkategori baik ditunjukkan dengan tercapainya target jumlah dan pertumbuhan pohon dan meningkatnya kapasitas SDM serta terbangunnya usaha mandiri pada masyarakat eks perambah yang menjadi peserta program.